2016
DOI: 10.1007/978-3-319-42417-0_32
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Synthetic Tutor Assistant: The EASEL Project and its Architecture

Abstract: Abstract. Robots are gradually but steadily being introduced in our daily lives. A paramount application is that of education, where robots can assume the role of a tutor, a peer or simply a tool to help learners in a specific knowledge domain. Such endeavor posits specific challenges: affective social behavior, proper modelling of the learner's progress, discrimination of the learner's utterances, expressions and mental states, which, in turn, require an integrated architecture combining perception, cognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…HRI scenarios Two interactive scenarios, developed to explore HRI in an educational context (Expressive agents for Symbiotic Education and Learning, EASEL [16], [17]) were used for data collection. Both scenarios had been pretested for suitability as a social and educational interaction for the age groups in this study.…”
Section: Methodsmentioning
confidence: 99%
“…HRI scenarios Two interactive scenarios, developed to explore HRI in an educational context (Expressive agents for Symbiotic Education and Learning, EASEL [16], [17]) were used for data collection. Both scenarios had been pretested for suitability as a social and educational interaction for the age groups in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Prior research has shown that young children will not only treat social robots as companions and guides (Belpaeme et al, 2012;Kahn et al, 2012;Shiomi et al, 2015), but will also readily learn new information from them (Breazeal et al, 2016;Kennedy et al, 2016;Movellan et al, 2009;Tanaka and Matsuzoe, 2012;Vouloutsi et al, 2016).…”
mentioning
confidence: 98%
“…2. Please refer to [24] for details. The modules interacts with each other: (1) The DM generates behaviour specifications transmitted to the BR; (2) The BR converts the behaviour specifications into platform-specific commands to the ACE; (3) The ACE executes the commands and delivers feedback to the BR about planning and execution of the commands; (4) The BR provides higher level feedback to the DM about the behaviour progression.…”
Section: Technical Implementationmentioning
confidence: 99%